Serumpun Bambu Sejuta Karya: Pengelolaan Potensi Kreatif sebagai Motor Ekonomi Lokal di Desa Gunung Riut Kabupaten Balangan - Putri, Agustia Rinjani; An'amta, Dimas Asto Aji; Afwillah; Rahmah, Mutia; Fadilatin, Umi; Gustiyanur; Baiti, Noor; Syafii, Ahmad; Mailiana; Syalehah; Nirmalasari, Indah (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2025)
This community service program was implemented in Gunung Riut Village, Halong District, Balangan Regency, South Kalimantan, an area with abundant bamboo resources and strong economic and cultural value. This potential has not been optimally utilized as a driver of the village's creative economy. The main problem lies in the weak capacity of local institutions, particularly the Karang Taruna youth organization, which has not been actively involved in productive activities such as making bamboo chairs and other derivative products. This program uses a Participatory Action Research (PAR) approach that places the community as the main subject or actor in the process of planning, implementing, and evaluating activities. The program aims to increase the independence of the community and village youth in managing local potential in a sustainable and economically valuable manner. The activities were carried out over a month using participatory methods, including socialization, coordination with local craftsmen, procurement of tools and materials for the pre-workshop, and a workshop on developing the creative potential of the village, involving four villages around Mount Riut. The results of the activities showed an increase in the technical skills of the participants in processing bamboo into marketable products, an increase in collective awareness of local economic potential, and the growth of motivation among young people to become entrepreneurs. In addition, this program succeeded in revitalizing the role of Karang Taruna as the driving force behind the village's creative economy and strengthening collaboration between villages. This program is expected to become an applicable model of empowerment based on local potential.